Expanded carrier screening for autosomal recessive conditions in health care: Arguments for a couple‐based approach and examination of couples' views. (28th February 2019) - Plantinga, Mirjam; Birnie, Erwin; Schuurmans, Juliette; Buitenhuis, Anne H.; Boersma, Elise; Lucassen, Anneke M.; Verkerk, Marian A.; van Langen, Irene M.; Ranchor, Adelita V.
Abstract: Background: Expanded carrier screening (ECS) is aimed at detecting carrier states for autosomal recessive (AR) or X‐linked conditions in couples from the general population planning a pregnancy. ECS is currently usually offered on an individual basis despite the fact that, for AR conditions, only carrier couples are at risk of affected offspring. In this paper, we present a couple‐based ECS test‐offer for AR conditions, where results are offered as couple‐results only, and describe how couples view such an offer. Methods and results: An online survey covering attitudes, perceived difficulty, and intention to take up couple‐based ECS was used to examine couples' views. Results show that in 76% of the participating couples there is no objection at all towards receiving couple‐results only. Most couples display similar views. Observed discrepancies usually involved one of the couple members having a positive view, whilst the other was neutral. Although views stayed strikingly stable after discussion, the partner's opinion was regarded as important in deciding whether or not to have testing. Conclusion: This study shows that most couples do not object to receiving couple rather than individual ECS results, have similar views towards the offer, and are able to discuss differences in views and intentions. Abstract : What's already known about this topic? Expanded carrier screening (ECS) has become widely available ECS is usually offered on individual basis, and individual carrier states are reported Views of potential individual users have been researched What does this study add? A couple‐based ECS test‐offer for autosomal recessive conditions, where results are offered as couple‐results only An examination of couples' views towards this offer: most couples do not object to receiving couple‐results only